Arginine Therapy for Lung Diseases - Scott, Jeremy A.; Maarsingh, Harm; Holguin, Fernando; Grasemann, Hartmut (Frontiers in Pharmacology, 2021)
Nitric oxide (NO) is produced by a family of isoenzymes, nitric oxide synthases NOSs), which all utilize L-arginine as substrate. The production of NO in the lung and airways can play a number of roles during lung development, regulates airway and vascular smooth muscle tone, and is involved in inflammatory processes and host defense. Altered L-arginine/NO homeostasis, due to the accumulation of endogenous NOS inhibitors and competition for substrate with the arginase enzymes, has been found to play a role in various conditions affecting the lung and in pulmonary diseases, such as asthma, chronic obstructive pulmonary disease (COPD), cystic fibrosis (CF), pulmonary hypertension, and bronchopulmonary dysplasia. Different therapeutic strategies to increase L-arginine levels or bioavailability are currently being explored in pre-clinical and clinical studies. These include supplementation of L-arginine or L-citrulline and inhibition of arginase.